Radiation-induced undifferentiated spindle cell sarcoma following high-dose-rate interstitial brachytherapy for tongue squamous cell carcinoma - Uchimoto, Yuka; Shimamoto, Hiroaki; Takeshita, Ami; Oya, Kaori; Kishino, Mitsunobu; Fukuda, Yasuo; Toyosawa, Satoru; Oda, Michio; Ogawa, Kazuhiko; Kreiborg, Sven; Mallya, Sanjay; Murakami, Shumei (Journal of Contemporary Brachytherapy, 2022)
High-dose-rate interstitial brachytherapy (HDR-ISBT) has recently come to be considered one of the most effective treatments for oral cancer. On the other hand, it is important to note that radiation therapy has some side effects. Especially, radiation-induced malignancy is probably the most serious complication affecting long-term survivors. We report a case of a radiation-induced undifferentiated spindle cell sarcoma that developed following HDR-ISBT for tongue squamous cell carcinoma (SCC). A 39-year-old woman with right tongue SCC underwent HDR-ISBT (60 Gy, 10 fractions, 8 days) treatment. Five years and one month later, a tumor had developed at the primary site. Surgery was performed for the tumor, which was histopathologically diagnosed as an undifferentiated spindle cell sarcoma. That was distinct from the squamous cell origin of the primary cancer. According to recently established criteria for radiation-induced malignancy, this case was classified as a radiation-induced sarcoma. A search of the literature revealed no previous report of radiation-induced malignancy following HDR-ISBT for tongue cancer.